Analisis Perbandingan Biaya dan Waktu Pekerjaan Antara Box Culver Convensional dan Box Culver Pra Cetak Pada Proyek Pembangunan Jalan Oma – Wassu Pulau Haruku - Hattu, Glen Michell; Lewakabessy, Godfried; Kakaly, Sulastri (CV. KAMPUS AKADEMIK PUBLISING, 2025)
In the thesis research analysis of the comparative cost and time of work between conventional box culverts and precast box culverts in the Oma – Wassu Road Construction Project, Haruku Island, there are two concrete work methods used, namely the conventional method and the precast method. If it is in the field, printing or casting area is needed, but if it is done in a factory, it does not require land, but requires transportation, transportation. For precast construction, the implementation is faster than conventional construction because the production process can be carried out simultaneously with the implementation of the structure.Through this study, an analysis of the cost and time required for Box Culvert work will be carried out to determine the level of efficiency and effectiveness between the conventional method and the precast method, as a reference for consideration and input for companies in making decisions related to project implementation methods. Through this study, an analysis of the cost and time required for Box Culvert work will be carried out to determine the level of efficiency and effectiveness between the conventional method and the precast method, as a reference for consideration and input for companies in making decisions related to project implementation methods. From the results of the research on the cost budget comparison plan that has been carried out, it can be concluded, first, that the cost for the implementation of conventional box culvert work is Rp. 200,154,452,000, while for the implementation of precast box culvert work is Rp. 1,520,908,000. The second is for the implementation time of conventional concrete box culvert work on the Oma – Wassu Road Construction Project for mobilization for 9 weeks plus Divisions 3 and 7 for 2 weeks, then the total is 11 weeks of work and the implementation of pre-cast box culverts is 15 weeks of work.